VKH-like uveitis during donafenib therapy for hepatocellular carcinoma: a case report and review of the literature - Liu, Rui; Liu, Guina; Lu, Fang (Frontiers in Pharmacology, 2024)
Background: The incidence of uveitis has risen with the use of targeted therapies, particularly prevalent in the administration of immune checkpoint inhibitors and MAP-kinase pathway inhibitors. We report the first case of VKH-like uveitis linked to Donafenib employed for the primary hepatocellular carcinoma, highlighting the necessity of ophthalmological follow-up in patients undergoing treatment with Donafenib. Case Presentation: A 55-year-old man developed VKH-like symptoms, including sporadic white patches, tinnitus, headache, and mild bilateral vision reduction, after 18 months of treatment with Donafenib and Sintilimab for hepatocellular carcinoma. Based on ophthalmological examinations that fundus fluorescein angiography images demonstrating multiple focal areas of pinpoint hyperfluorescence, along with pooling indicative of neurosensory detachment and disc leakage in both eyes, choroid thickening in swept-source optical coherence tomography, and “sunset-glow” fundus appearance, a tentative diagnosis of VKH-like uveitis was made. Initially, his best-corrected visual acuity (BCVA) was 20/200 in the right eye and 20/80 in the left eye. Upon discontinuing Donafenib and starting a 3-month course of oral glucocorticoids, his BCVA improved to 20/30 in the right eye and 20/40 in the left eye. Conclusion: Targeted drugs have been commonly used for cancer treatment in recent years, but challenges of ocular side effects emerged gradually. To optimize patient outcomes, regular ophthalmological follow-ups are essential for those undergoing treatment with targeted therapies like Donafenib.